Research on information retrieval model under scarcity theory and user cognition. (June 2019) - Ruixiang, Ou; Yao, Huang; Feng, Pan; Hui, Pan
Abstract: In essence, information retrieval is a cognitive process, which is the matching process between the reader's or user's cognition and the system's pre-set cognition. At present, cognitive view has become a research hotspot in the field of information retrieval. The research of information retrieval cognitive model has laid a theoretical foundation for the development of information retrieval system. Based on scarcity theory, this paper analyses the dynamic change of user's cognitive ability and constructs a cognitive model of information retrieval based on scarcity theory. After analysis, this paper evaluates the effect of information retrieval cognitive model based on scarcity theory, and clarifies the specific problems that the model can solve.